Gender-responsive governance among unit heads in higher education institutions - Laganhon, Aljaven Bruce C. (Edelweiss Applied Science and Technology, 2025)
Effective management styles in higher learning institutions are critical for ensuring equal access to opportunities and development for both men and women, thereby enhancing organizational productivity and performance. This study aimed to determine gender-responsive governance among unit heads of higher education institutions (HEIs) in Negros Occidental during the school year 2021-2022. Using a descriptive-correlational and comparative research design, the study explored relationships between gender-responsive governance and variables such as age, sex, length of service, and educational qualification. The respondents were 94 unit heads from three state universities and colleges (SUCs). Data were collected using the Gender Responsiveness Governance Tool and analyzed through SPSS with descriptive statistics, Pearson’s correlation, Mann-Whitney U test, and Kruskal-Wallis H test. Results indicated a moderate level of gender-responsive governance (M = 53.80, SD = 19.99), with older respondents demonstrating higher responsiveness. No significant differences were found regarding sex, length of service, or educational qualification. The study concludes that promoting gender-responsive governance requires targeted interventions, particularly for younger unit heads. Practical implications suggest that institutional leadership training and policy development should prioritize building gender competence across all managerial levels to foster inclusive, equitable, and effective organizational environments.